Surge protection for interface circuits of communication system. - Qingheng Chen
Microelectronic circuits are often damaged by surges. Surge protection for microelectronic circuits has some special requirements that are different than those for electrical equipment. The approach that the surge invades microelectronic circuits is studied in this paper. The surge withstand capability of some typical serial communication integrated chips, the behaviors of voltage-limiting components, and the influence of the connecting capacitance of a voltage-clamping device on digital signals are studied. Then, a design method of surge suppressor for communication systems is proposed.
Keywords: Capacitance; Communication system; Digital signals; Electrical equipment; Microelectronic circuits; Serial communication integrated chips; Surge protection; Surge withstand capability; Voltage-clamping device; Voltage-limiting components